The music of Israel from the biblical era to modern timess - Gradenwitz, Peter 1910-2001 (Amadeus Press, 1996)
Incorporating the most recent historical discoveries and research of both Israeli and international scholars, Gradenwitz traces the rise and growth of Hebrew and Jewish music from its earliest beginnings to the present and examines the background and state of musical life in Israel today. As in the previous volume, the author explores all historical and musical aspects of ancient, medieval, and modern Hebrew liturgical and Jewish secular music, pointing out Jewish contributions to world music and examining musical cross-relations between the Jews of the Holy Land and those of the Diaspora